Indikator Kemahiran Employability dalam Kalangan Graduan Pendidikan (Sains Humanika, 2018)
The phenomenon of unemployment problem among graduates is not a new issue. In fact, it also involves graduates who hold an education degree. Hence, this study was conducted to determine the indicators of employability skills needed by the education graduates especially from technical and vocational education field in Malaysia. This study was conducted qualitatively through interview among five experts.  Respondents were among those with experiences in teaching and working in technical and vocational education field.  Results showed that there were nine elements of employability skills needed to be mastered by graduates in technical and vocational education.  These indicators are communication skills, creative and critical thinking skills, information management skills, self-management skills, teamwork and cooperation skills, leadership skills, ethics and moral professionalism, entrepreneurial skills and social skills.  The mastery of these employability skills are deemed important in order to produce teachers with highly qualified and competitive professionals.
Keywords: Employability skills; education graduates; technical and vocational; interview